2011
DOI: 10.1063/1.3660159
|View full text |Cite
|
Sign up to set email alerts
|

Logical stochastic resonance with correlated internal and external noises in a synthetic biological logic block

Abstract: Following the advent of synthetic biology, several gene networks have been engineered to emulate digital devices, with the ability to program cells for different applications. In this work, we adapt the concept of logical stochastic resonance to a synthetic gene network derived from a bacteriophage λ. The intriguing results of this study show that it is possible to build a biological logic block that can emulate or switch from the AND to the OR gate functionalities through externally tuning the system paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…(Others have termed this the “sense signal” which is then compared to an inner “reference signal,” triggering the “error signal.” 89 ) These changes are then indeed compared to the desired states and reaction thresholds (basal homeostatic and limiter motifs of negative feedback, shown at right); which triggers a corrective response that reverses the trend, bringing the system back into balance (like the home furnace). While perhaps neglected in cybernetic models of human behavior, this coupled feedback configuration has been noted elsewhere and deemed a biological logic gate or block that can switch from the “and” to the “or” functions, 141 the logic circuitry of the electrical transistors in computer chips.…”
Section: Behavior Feedback and The Emergence Of Self-regulatory Codementioning
confidence: 99%
“…(Others have termed this the “sense signal” which is then compared to an inner “reference signal,” triggering the “error signal.” 89 ) These changes are then indeed compared to the desired states and reaction thresholds (basal homeostatic and limiter motifs of negative feedback, shown at right); which triggers a corrective response that reverses the trend, bringing the system back into balance (like the home furnace). While perhaps neglected in cybernetic models of human behavior, this coupled feedback configuration has been noted elsewhere and deemed a biological logic gate or block that can switch from the “and” to the “or” functions, 141 the logic circuitry of the electrical transistors in computer chips.…”
Section: Behavior Feedback and The Emergence Of Self-regulatory Codementioning
confidence: 99%
“…The inclusion of several studies in this issue applying stochastic dynamics to gene networks and systems biology is indicative of the extent to which stochastic dynamics has extended its reach in recent years. Dari et al 72 offer a genetic module that can perform the AND/OR gate functionalities in the presence of noise, following the logical stochastic resonance paradigm. The effects of connection topology and time-delayed coupling on the dynamics of genetic regulatory small-world networks are studied by Yang et al 73 For a fixed network topology, the phenomenon of delay-induced resonance is revealed.…”
Section: Introduction To Focus Issue: Nonlinear and Stochastic Physicmentioning
confidence: 99%
“…89 ) These changes are then indeed compared to the desired states and reaction thresholds (basal homeostatic and limiter motifs of negative feedback, shown at right); which triggers a corrective response that reverses the trend, bringing the system back into balance (like the home furnace). While perhaps neglected in cybernetic models of human behavior, this coupled feedback configuration has been noted elsewhere and deemed a biological logic gate or block that can switch from the "and" to the "or" functions, 141 the logic circuitry of the electrical transistors in computer chips.…”
Section: Feedback Functions Of Cellular Receptor Complexesmentioning
confidence: 99%